A young COVID-19 patient with mild symptoms and disseminated intravascular coagulation - Kumar, Abhishek; Kumar, Piyush; Dungdung, Ajit (International Journal of Research in Medical Sciences, 2020)
Covid-19 pandemic in recent times has emerged as a major contributor to multisystemic thrombosis and related complications. Covid-19 leads to a syndrome of generalised systemic coagulopathy and acquired thrombophilia which manifests itself in the form of arterial, venous and microvascular thrombosis. The pathological mechanisms for covid-19 induced coagulopathy are yet to be clear however extensive research is underway and multiple insights have emerged recently. Here we report a case of young Covid-19 patient who presented with mild fever but severely deranged coagulation parameters and inflammatory markers. He was managed conservatively with Low molecular weight heparin, Fresh frozen plasma, Tab HCQS, Tab Doxycycline, Tab Ivermectin, Tab Zinc, Tab Vitamin C and responded well to treatment. He was later discharged after testing covid-19 negative. Screening of all confirmed cases for coagulopathy like D-dimer, FDP, platelet count, Prothrombin time may be done to identify high risk asymptomatic/mild cases which may cause further decrease in mortality.